The Effects of Inspiratory Muscle Training in Neuromuscular Disorders: Review Article - Okta Hariza; Budiati Lasmitasari; Siti Chandra Widjanantie; Nury Nusdwinuringtyas (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Progressive inspiratory muscles weakness in neuromuscular disorders (NMD) can lead to respiratory impairments, from restrictive lung to respiratory failure. Inspiratory muscle training (IMT) is an exercise with a device to increase inspiratory muscles strength and/or endurance. This article wasaimed to review the effect and prescription of IMT in NMD subjects.Methods: Searching method was done in PubMed and Google Scholar using keywords: “inspiratory muscle training” AND “neuromuscular disorders” AND “MIP” OR “PImax”.Results: Seven related studies were found. These studies shown that IMT increased inspiratory muscles strength and/or endurance in chronic progressive NMD. Most studies used threshold type. The intensities varied from 30% through 70% of maximum inspiratory pressure (MIP), minimum twice a day. Therepetition for strengthening was 10 times with 20-seconds rest between repetitions. Endurance trainings were done in 10 cycles of 1-minute breathing or for total 20 m inutes.Conclusion: Several evidences reported that IMT significantly improve strength and endurance of inspiratory muscles in chronic progressive NMD. It was effective in earlier phase of NMD. The minimum load intensity was 30% MIP.Keywords: Inspiratory muscle training (IMT), neuromuscular disorders (NMD), maximum inspiratory pressure (MIP)